Border cinema : reimagining identity through aesthetics - Hanna, Monica; Sheehan, Rebecca, 1979- (Rutgers University Press, 2019)
The rise of digital media and globalization's intensification since the 1990s have significantly refigured global cinema's form and content. The coincidence of digitization and globalization has produced what this book helps to define and describe as a flourishing border cinema whose aesthetics reflect, construct, intervene in, denature, and reconfigure geopolitical borders. This collection demonstrates how border cinema resists contemporary border fortification processes. Showing how cinematic media have functioned technologically and aesthetically to engender contemporary shifts in national and individual identities, the contributors also propose alternative conceptions of these identities to those promulgated by the often restrictive current political rhetoric and ideologies that represent a backlash to globalization.
Keywords: Boundaries in motion pictures.; Identity (Psychology) in motion pictures.; Motion pictures -- Aesthetics.; Digital cinematography.; Frontières au cinéma.; Identité (Psychologie) au cinéma.; Cinéma -- Esthétique.; Cinéma numérique.; PERFORMING ARTS -- General.; Boundaries in motion pictures; Digital cinematography; Identity (Psychology) in motion pictures; Motion pictures -- Aesthetics; Film; Grenze -- Motiv; Globalisierung -- Motiv; Identität -- Motiv; media, digital media, borders, global, globalization, digital, cinema, geopolitical, regional border, global cinema.